Detection of earth faults in electric power cables by analyzing changes in the short-circuit resistance - Wojtas, P.; Kozłowski, A.; Kryca, M.; Miedziński, B. (Электрические контакты и электроды, 2014)
Paper presents method of earth faults detection in electric power cables based on measurement and analysis of the short circuit resistance value in transient under mechanical bumps exerted on the faulty cable line during detection procedure. Discussed investigated results and formulates conclusions for use in practice. Предложен метод обнаружения дефектов заземления в электрических силовых кабелях, основанный на измерении и анализе сопротивления короткого замыкания при кратковременных механических ударах (толчках), прикладываемых к дефектному кабелю в процессе испытаний. Обсуждаются полученные результаты и формулируются практические рекомендации. Запропоновано метод виявлення дефектів заземлення в електричних силових кабелях, заснований на вимірюванні та аналізі опору короткого замикання при короткочасних механічних ударах (поштовхах), що прикладаються до дефектного кабелю в процесі випробувань. Обговорюються отримані результати і формулюються практичні рекомендації.